Free-field sound radiation measurement with multiple synchronous cameras. (January 2022) - Gardonio, Paolo; Rinaldo, Roberto; Dal Bo, Loris; Del Sal, Roberto; Turco, Emanuele; Fusiello, Andrea
Highlights: Vibration measurement with multiple cameras (i.e. two or more cameras). Sound radiation estimate from flexural vibration measurements with multiple cameras. Intrinsic compensation of flexural vibration measurement errors by direct boundary integral for sound radiation estimate. Abstract: This paper investigates the possibility of using photogrammetry to obtain the sound radiation into free-field from flexural vibrations of distributed thin structures. A simple model problem is considered, where multiple (i.e. two or more) cameras are used to track at a regular grid of target points the flexural vibration of a baffled thin rectangular flat plate structure. The sound radiation into free-field is then derived from the Rayleigh integral, which is approximated into a finite sum assuming the plate is discretised into a regular mesh of elements whose centres correspond to the grid of points where the flexural vibrations are measured with the cameras. The paper shows that the vibration measurement errors produced by the image pixelisation in the cameras compensate over the grid of target points so that the estimate of the radiated sound field with the Rayleigh integral formulation is comparatively more accurate.